A water-based modified pressure-sensitive adhesive and its preparation method and application
By using water-based modified pressure-sensitive adhesive in the GDL bonding process and using hydrogen bonding and polymerization network technology, the problems of insufficient bonding strength and glue migration in the prior art are solved, and efficient GDL bonding and stable performance are achieved.
Patent Information
- Application Number
- CN202310845742.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-07-11
AI Technical Summary
In the existing GDL bonding process, thermosetting glue can easily lead to warping and deformation, and photostanding glue has the risk of not being completely cured. In high-pressure, high humidity and high temperature environment, the pressure-sensitive glue may migrate, affecting the performance of the membrane electrode.
Water-based modified pressure-sensitive adhesive is used, which includes water-based pressure-sensitive adhesive latex, water-soluble crystalline polymer and acrylamide, which is formed by hydrogen bond interaction and polymerization network, significantly improving the bond strength and inhibiting glue migration.
While meeting the room temperature bonding process requirements, the bonding strength between GDL and the substrate is significantly improved, and the migration of pressure-sensitive adhesive in GDL is effectively suppressed, preventing the influence on the performance of the film electrode.
Smart Images

Figure CN116904145B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials and fuel cells, and in particular to a water-based modified pressure-sensitive adhesive and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC) is composed of multiple single cells connected in series, and each single cell is mainly composed of membrane electrode assembly (MEA) and bipolar plate. MEA is the core component of PEMFC and is a key factor affecting PEMFC specific power density, energy density distribution and working life. MEA is mainly composed of catalyst layer (CL), proton exchange membrane (PEM) and gas diffusion layer (GDL). The mainstream MEA preparation method is to coat or thermally transfer the catalyst on both sides of PEM to obtain catalyst coated proton membrane (CCM), and then bond the CCM to the support material with adhesive to obtain a five-in-one sample, and then bond the GDL to the support material with adhesive to obtain a seven-in-one MEA.
[0003] At present, the mainstream GDL bonding method is to apply adhesive to the four sides of the GDL through the glue dispensing process, and then bond it to the supporting materials around the five-in-one sample. However, for this GDL bonding process, since thermosetting glue needs to be cured at high temperature, it is easy to cause the GDL and supporting materials to warp and deform. Because the light-curing glue needs to be dispensed on the black, opaque, porous GDL, there is a risk that the light-curing glue that penetrates into the GDL cannot be completely cured. Therefore, for the current process, the better GDL glue needs to meet the requirements of initial adhesion and good low-temperature bonding of GDL and supporting materials. Pressure-sensitive glue is currently the most commonly used GDL bonding glue.
[0004] However, when dozens or hundreds of MEAs are assembled into a PEMFC stack, several tons of pressure need to be applied to them through the end plates to ensure the sealing of the single cell and the stack. Compared with the active area, the thickness of the MEA and especially the GDL glue line area is the largest, so the GDL glue line is under the greatest pressure. Therefore, when assembling the stack, the pressure-sensitive adhesive line is prone to widening or further penetration into the GDL. At the same time, under the operating environment of high pressure, high humidity and high temperature, the pressure-sensitive adhesive may migrate after long-term operation, affecting the pores in the GDL active area and even contaminating the catalyst layer, thereby affecting the membrane electrode performance. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a water-based modified pressure-sensitive adhesive and its preparation method and application. The method of the present invention can significantly increase the bonding strength of the pressure-sensitive adhesive to the fuel cell membrane electrode gas diffusion layer and the frame material without affecting the room temperature bonding process, and significantly inhibit the migration of the pressure-sensitive adhesive in the gas diffusion layer under pressure.
[0006] To achieve the above-mentioned purpose, in a first aspect, the present invention provides a water-based modified pressure-sensitive adhesive, comprising a water-based pressure-sensitive adhesive emulsion, a water-soluble crystalline polymer and polyacrylamide, wherein the polyacrylamide is obtained by reacting an acrylamide monomer, a free radical initiator and a cross-linking agent, the water-based pressure-sensitive adhesive emulsion is an acrylate water-based pressure-sensitive adhesive or a polyurethane water-based pressure-sensitive adhesive, the glass transition temperature of the water-soluble crystalline polymer is greater than 90°C, and the water-soluble crystalline polymer contains a hydrogen bond donor functional group or a hydrogen bond acceptor functional group.
[0007] In the present invention, a water-soluble crystalline polymer with a high glass transition temperature and an acrylamide polymerization system that can form hydrogen bond interactions with pressure-sensitive adhesive components are added to the currently commonly used commercial polyacrylate or polyurethane water-based pressure-sensitive adhesive. Under the premise of not affecting the current GDL dispensing process and meeting the room temperature bonding requirements, the rigidity of the gas diffusion layer pressure-sensitive adhesive is gradually increased in two steps, the bonding strength of the gas diffusion layer between the GDL and the frame material is significantly improved, and the migration of the pressure-sensitive adhesive in the GDL can be effectively suppressed during the pressing and bonding process and the operation of the PEMFC.
[0008] If the glass transition temperature of the water-soluble crystalline polymer is too low, it is difficult to effectively increase the rigidity of the pressure-sensitive adhesive to effectively inhibit the migration of the adhesive during the lamination and bonding process between the GDL and the supporting material and the subsequent operation of the PEMFC.
[0009] The two-step method gradually increases the rigidity of the room temperature adhesive water-based pressure-sensitive adhesive. The first step of inhibiting the migration of GDL glue is to add a water-soluble crystalline polymer with a high glass transition temperature (Tg>90°C) that can interact with the functional groups in the pressure-sensitive adhesive molecules through hydrogen bonds to the current commercial water-based pressure-sensitive adhesive latex. Since the water-soluble crystalline polymer has crystallinity, a crystalline micro-domain can be formed in the pressure-sensitive adhesive. The molecular chain of the dense micro-domain has multiple functional groups that can form hydrogen bonds with the pressure-sensitive adhesive molecules. The crystalline micro-domain with relatively high strength acts as a physical cross-linking point to increase the physical cross-linking density in the pressure-sensitive adhesive system, thereby increasing the rigidity of the pressure-sensitive adhesive, so that it maintains its shape and is not easy to deform and migrate when it is pressed and bonded to the support material after the GDL glue is dried or during the subsequent pressure process of PEMFC operation.
[0010] The two-step method gradually increases the rigidity of the gas diffusion layer pressure-sensitive adhesive. The second step refers to adding acrylamide monomers, free radical initiators and crosslinkers that are not volatile, soluble in water and easy to polymerize to the current commercial water-based pressure-sensitive adhesive emulsion, which is conducive to further improving the creep resistance of the pressure-sensitive adhesive and does not affect the GDL dispensing and bonding process. Additives such as acrylamide do not play a role in the dispensing and bonding process. The pressure-sensitive adhesive will not lose its initial viscosity due to the high degree of crosslinking and hardening of the system, and it will not be able to bond the GDL and frame materials at room temperature. When the PEMFC starts to operate and the temperature rises, the acrylamide monomers and crosslinkers in the pressure-sensitive adhesive matrix polymerize to form a pure hard three-dimensional crosslinked network, further enhancing the rigidity of the pressure-sensitive adhesive, thereby inhibiting the migration of the pressure-sensitive adhesive during the operation of the stack. At this time, the loss of initial viscosity of the pressure-sensitive adhesive due to hardening will not have a negative impact on the stack, because the GDL and the frame have been pressed together with tons of pressure, and the bonding and positioning functions have been completed.
[0011] Preferably, the water-soluble crystalline polymer is 10-150% of the solid mass of the water-based pressure-sensitive adhesive; the acrylamide monomer is 1-10% of the total mass of the water-based pressure-sensitive adhesive solid and the water-soluble crystalline polymer; the free radical initiator is 0.5-2% of the mass of the acrylamide monomer; and the cross-linking agent is 0.5-5% of the mass of the acrylamide monomer.
[0012] Preferably, the hydrogen bond donor functional group is at least one of an amide bond, a carboxylate, a sulfonate, a hydroxyl, a primary amine, and a secondary amine.
[0013] More preferably, the water-soluble crystalline polymer is at least one of polyacrylamide, urea-formaldehyde resin, polyallylamine, perfluorosulfonic acid resin, and polyacrylic acid.
[0014] Preferably, the hydrogen bond acceptor functional group is at least one of an ether bond, a tertiary amine, an epoxy bond, a hydroxyl group, a carboxylic acid, an amide bond, a carboxylate, a sulfonate, and a carbon-fluorine bond.
[0015] More preferably, the water-soluble crystalline polymer is at least one of polyvinyl alcohol, polyethylene oxide, urea-formaldehyde resin, perfluorosulfonic acid resin, and polyacrylic acid.
[0016] In the present invention, polyacrylamide, polyvinyl alcohol, polyoxyethylene, urea-formaldehyde resin, polyallylamine, perfluorosulfonic acid resin, and polyacrylic acid have functional groups such as amide, hydroxyl, amino, and acid radical. The strongly electronegative oxygen or nitrogen atoms and the strongly polar hydrogen atoms in the functional groups such as amide, hydroxyl, amino, and acid radical can form hydrogen bonds with functional groups such as carboxylate, isocyanate, and urethane bonds in the pressure-sensitive adhesive, which is beneficial to further improve the crosslinking density in the pressure-sensitive adhesive system, thereby further increasing the rigidity of the pressure-sensitive adhesive.
[0017] Preferably, the aqueous pressure-sensitive adhesive emulsion is an aqueous acrylate pressure-sensitive adhesive or an aqueous polyurethane pressure-sensitive adhesive.
[0018] Preferably, the free radical initiator is a thermally initiated free radical initiator at 60-80° C. More preferably, the free radical initiator is at least one of potassium persulfate, benzoyl peroxide, and azobisisobutyronitrile.
[0019] Preferably, the crosslinking agent is bisacrylamide. More preferably, the crosslinking agent is N,N′-methylenebisacrylamide.
[0020] In the present invention, if the amount of acrylamide monomer and crosslinking agent added is too low, it is difficult to thermally initiate polymerization during PEMFC operation to effectively enhance the pressure-sensitive adhesive. If the amount of acrylamide monomer and crosslinking agent added is too high, it will affect the initial performance of the pressure-sensitive adhesive during GDL dispensing and cause deformation of the pressure-sensitive adhesive during press assembly.
[0021] In a second aspect, the present invention provides a method for preparing the above-mentioned water-based modified pressure-sensitive adhesive, comprising the following steps:
[0022] S1: adding acrylamide monomer, free radical initiator and crosslinking agent to the aqueous solution of water-soluble crystalline polymer at a temperature of 20-60° C., mixing evenly to obtain a mixed aqueous solution;
[0023] S2: Add water-based pressure-sensitive adhesive latex to the mixed aqueous solution in S1 at a temperature of 20-60° C. and mix evenly to obtain a water-based modified pressure-sensitive adhesive.
[0024] In a third aspect, the present invention provides an application of a water-based modified pressure-sensitive adhesive in a membrane electrode gas diffusion layer, the application comprising the following steps: coating the above-prepared water-based modified pressure-sensitive adhesive on the surface of the porous layer of the gas diffusion layer, and pressing it with a five-in-one membrane electrode after drying to obtain a seven-in-one membrane electrode.
[0025] Preferably, the coating method is dispensing or spraying.
[0026] Preferably, the drying conditions are: temperature 20-60° C., and drying time 1-60 min.
[0027] Preferably, the pressing conditions are: pressure 0.05-0.5Mpa, pressing time 1-60s.
[0028] In the present invention, if the pressure is too small, it is easy to affect the bonding effect of the water-based modified pressure-sensitive adhesive; if the pressure is too large, it will cause excessive compression of the GDL.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention adds a high Tg water-soluble crystalline polymer that can form hydrogen bonds with pressure-sensitive adhesive molecules and an appropriate amount of acrylamide polymerization system to an acrylic acid-based water-based pressure-sensitive adhesive or a polyurethane-based water-based pressure-sensitive adhesive. While meeting the current conventional process requirements for GDL bonding, the bonding strength between the GDL and the substrate at room temperature can be significantly improved, and the migration problem of the pressure-sensitive adhesive in the GDL during pressing and PEMFC operation can be effectively suppressed, effectively preventing the adverse effects of GDL glue migration on the membrane electrode and PEMFC performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the mobility of GDL glue in Example 1 of the present invention.
[0032] Figure 2 It is a schematic diagram of the mobility of GDL glue in Comparative Example 1 of the present invention.
[0033] Figure 3 It is a schematic diagram of the mobility of GDL glue in Comparative Example 3 of the present invention.
[0034] Figure 4 It is a schematic diagram of the mobility of GDL glue in Comparative Example 4 of the present invention.
[0035] Figure 5 It is a schematic diagram of the mobility of GDL glue in Comparative Example 6 of the present invention.
[0036] Figure 6 It is a schematic diagram of the mobility of GDL glue in Comparative Example 7 of the present invention. DETAILED DESCRIPTION
[0037] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments, but the protection scope and implementation methods of the present invention are not limited thereto.
[0038] Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0039] Example 1
[0040] This embodiment discloses a water-based modified pressure-sensitive adhesive, which includes a water-based pressure-sensitive adhesive emulsion, a water-soluble crystalline polymer and polyacrylamide. The polyacrylamide is obtained by reacting acrylamide monomer, a free radical initiator and a cross-linking agent.
[0041] In this embodiment, the aqueous pressure-sensitive adhesive emulsion is an aqueous acrylic pressure-sensitive adhesive emulsion (solid content 55%), the manufacturer is 3M, the model is MAC-100; the water-soluble crystalline polymer is polyacrylamide (Tg = 188°C); the free radical initiator is potassium persulfate, and the cross-linking agent is N,N′-methylenebisacrylamide.
[0042] A method for preparing a water-based modified pressure-sensitive adhesive comprises the following steps:
[0043] S1: Add 6.6 g of polyacrylamide powder into 20 mL of deionized water, heat to 60°C, and stir magnetically at 1000 rpm for 60 min until the polyacrylamide is completely dissolved to obtain a polyacrylamide aqueous solution;
[0044] S2: Add 1.32 g of acrylamide monomer, 16.5 mg of potassium persulfate and 39.6 mg of N,N′-methylenebisacrylamide to the polyacrylamide aqueous solution in S1, and stir magnetically at 500 rpm for 10 min at 25°C to obtain a mixed aqueous solution;
[0045] S3: Add 20 g of water-based acrylic pressure-sensitive adhesive emulsion to the mixed aqueous solution in S2, stir magnetically at 500 rpm for 30 min at 25° C., and mix well to obtain a water-based modified pressure-sensitive adhesive.
[0046] In this embodiment, polyacrylamide accounts for 60% of the solid mass of the water-based pressure-sensitive adhesive; acrylamide monomer accounts for 7.5% of the total mass of the water-based pressure-sensitive adhesive solid and polyacrylamide; potassium persulfate accounts for 1.25% of the mass of acrylamide monomer; and N,N′-methylenebisacrylamide accounts for 3% of the mass of acrylamide monomer.
[0047] The present embodiment also discloses an application of a water-based modified pressure-sensitive adhesive in a membrane electrode gas diffusion layer. The water-based modified pressure-sensitive adhesive prepared above is dispensed on the surface of a GDL porous layer, with a glue line width of 1 mm and a dispense thickness of 20 μm. The mixture is dried at 25° C. for 30 min, and then the dispensed portion of the GDL porous layer is bonded to the portion of a five-in-one membrane electrode frame material, and pressed at 0.2 MPa for 15 s to obtain a seven-in-one membrane electrode assembly.
[0048] Example 2
[0049] This embodiment discloses a water-based modified pressure-sensitive adhesive, which includes a water-based pressure-sensitive adhesive emulsion, a water-soluble crystalline polymer and polyacrylamide. The polyacrylamide is obtained by reacting acrylamide monomer, a free radical initiator and a cross-linking agent.
[0050] In this embodiment, the aqueous pressure-sensitive adhesive emulsion is an aqueous polyurethane pressure-sensitive adhesive emulsion (solid content 65%), the manufacturer is Zoyan, and the model is ZY-7533; the water-soluble crystalline polymer is urea-formaldehyde resin (Tg=160°C); the free radical initiator is potassium persulfate, and the cross-linking agent is N,N′-methylenebisacrylamide.
[0051] A method for preparing a water-based modified pressure-sensitive adhesive comprises the following steps:
[0052] S1: Add 6.49 g of urea-formaldehyde resin powder into 30 mL of deionized water, heat to 60°C, and stir magnetically at 1000 rpm for 30 min. After the solution is completely dissolved, a urea-formaldehyde resin aqueous solution is obtained;
[0053] S2: Add 1.30 g of acrylamide monomer, 13 mg of potassium persulfate and 52 mg of N,N′-methylenebisacrylamide to the urea-formaldehyde resin aqueous solution in S1, and stir magnetically at 500 rpm for 10 min at 25°C to obtain a mixed aqueous solution;
[0054] S3: Add 30 g of polyurethane pressure-sensitive adhesive latex to the mixed aqueous solution in S2, stir magnetically at 500 rpm for 30 min at 25° C., and mix well to obtain a water-based modified pressure-sensitive adhesive.
[0055] In this embodiment, urea-formaldehyde resin accounts for 33.3% of the solid mass of the water-based pressure-sensitive adhesive; acrylamide monomer accounts for 5% of the total mass of the water-based pressure-sensitive adhesive solid and polyacrylamide; potassium persulfate accounts for 1% of the mass of the acrylamide monomer; and N,N′-methylenebisacrylamide accounts for 4% of the mass of the acrylamide monomer.
[0056] The present embodiment also discloses an application of a water-based modified pressure-sensitive adhesive in a membrane electrode gas diffusion layer. The water-based modified pressure-sensitive adhesive prepared above is dispensed on the surface of a GDL porous layer, with a glue line width of 1 mm and a dispense thickness of 20 μm. The mixture is dried at 25° C. for 30 min, and then the dispensed portion of the GDL porous layer is bonded to the portion of a five-in-one membrane electrode frame material, and pressed at 0.2 MPa for 10 s to obtain a seven-in-one membrane electrode assembly.
[0057] Example 3
[0058] The difference from Example 1 is that the mass of the aqueous pressure-sensitive adhesive emulsion is 20 g, the mass of polyacrylamide is 1.1 g; the mass of acrylamide monomer is 1.21 g; the mass of potassium persulfate is 0.605 mg; the mass of N,N′-methylenebisacrylamide is 0.605 mg; the aqueous pressure-sensitive adhesive emulsion is an aqueous acrylic pressure-sensitive adhesive emulsion (MAC-100 glue, 3M, solid content 55%);
[0059] Polyacrylamide is 10% of the solid mass of the water-based pressure-sensitive adhesive; acrylamide monomer is 1% of the total mass of the water-based pressure-sensitive adhesive solid and polyacrylamide; potassium persulfate is 0.5% of the mass of acrylamide monomer; N,N′-methylenebisacrylamide is 0.5% of the mass of acrylamide monomer, and the rest are the same as in Example 1.
[0060] Example 4
[0061] The difference from Example 1 is that the mass of the aqueous pressure-sensitive adhesive emulsion is 20 g, the mass of polyacrylamide is 16.5 g; the mass of acrylamide monomer is 2.75 g; the mass of potassium persulfate is 55 mg; the mass of N,N′-methylenebisacrylamide is 137.5 mg; the aqueous pressure-sensitive adhesive emulsion is an aqueous acrylic pressure-sensitive adhesive emulsion (MAC-100 glue, 3M, solid content 55%);
[0062] Polyacrylamide is 150% of the solid mass of the water-based pressure-sensitive adhesive; acrylamide monomer is 10% of the total mass of the water-based pressure-sensitive adhesive solid and the high molecular weight polymer; potassium persulfate is 2% of the mass of the acrylamide monomer; N,N′-methylenebisacrylamide is 5% of the mass of the acrylamide monomer, and the rest are the same as in Example 1.
[0063] Comparative Example 1
[0064] The water-based acrylic pressure-sensitive adhesive latex (55% solid content) was glued on the surface of the GDL porous layer, with a glue line width of 1 mm and a glue thickness of 20 μm. After drying at 25°C for 30 minutes, the glued part of the GDL porous layer was bonded to the part of the five-in-one membrane electrode frame material, and pressed at 0.2 MPa for 15 seconds to obtain a seven-in-one membrane electrode assembly.
[0065] Comparative Example 2
[0066] The difference from Example 1 is that the mass of the water-based acrylic pressure-sensitive adhesive emulsion (MAC-100 glue, 3M, solid content 55%) is 20 g; the mass of polyacrylamide is 22 g; the mass of acrylamide monomer is 330 mg; the mass of potassium persulfate is 1.65 mg; the mass of N,N′-methylenebisacrylamide is 1.65 mg;
[0067] Polyacrylamide is 200% of the solid mass of the water-based pressure-sensitive adhesive; acrylamide monomer is 1% of the total mass of the water-based pressure-sensitive adhesive solid and polyacrylamide; potassium persulfate is 0.5% of the mass of the acrylamide monomer; N,N′-methylenebisacrylamide is 0.5% of the mass of the acrylamide monomer, and the rest are the same as in Example 1.
[0068] Comparative Example 3
[0069] The difference from Example 1 is that the mass of the water-based acrylic pressure-sensitive adhesive emulsion (MAC-100 glue, 3M, solid content 55%) is 20 g, the mass of polyacrylamide is 0.55 g; the mass of acrylamide monomer is 1.155 g; the mass of potassium persulfate is 23.1 mg; the mass of N,N′-methylenebisacrylamide is 57.75 mg;
[0070] Polyacrylamide is 5% of the solid mass of the water-based pressure-sensitive adhesive; acrylamide monomer is 10% of the total mass of the water-based pressure-sensitive adhesive solid and the high molecular weight polymer; potassium persulfate is 2% of the mass of the acrylamide monomer; N,N′-methylenebisacrylamide is 5% of the mass of the acrylamide monomer, and the rest are the same as in Example 1.
[0071] Comparative Example 4
[0072] The difference from Example 1 is that the mass of the water-based acrylic pressure-sensitive adhesive emulsion (MAC-100 glue, 3M, solid content 55%) is 20 g, the mass of polyacrylamide is 11 g; the mass of acrylamide monomer is 110 mg; the mass of potassium persulfate is 0.22 mg; the mass of N,N′-methylenebisacrylamide is 0.22 mg;
[0073] Polyacrylamide is 100% of the solid mass of the water-based pressure-sensitive adhesive; acrylamide monomer is 0.5% of the total mass of the water-based pressure-sensitive adhesive solid and polyacrylamide; potassium persulfate is 0.2% of the mass of the acrylamide monomer; N,N′-methylenebisacrylamide is 0.2% of the mass of the acrylamide monomer, and the rest are the same as in Example 1.
[0074] Comparative Example 5
[0075] The difference from Example 1 is that the mass of the water-based acrylic pressure-sensitive adhesive emulsion (MAC-100 glue, 3M, solid content 55%) is 20 g, the mass of polyacrylamide is 11 g; the mass of acrylamide monomer is 4.4 g; the mass of potassium persulfate is 220 mg; the mass of N,N′-methylenebisacrylamide is 440 mg;
[0076] Polyacrylamide is 100% of the solid mass of the water-based pressure-sensitive adhesive; acrylamide monomer is 20% of the total mass of the water-based pressure-sensitive adhesive solid and polyacrylamide; potassium persulfate is 5% of the mass of the acrylamide monomer; N,N′-methylenebisacrylamide is 10% of the mass of the acrylamide monomer, and the rest are the same as in Example 1.
[0077] Comparative Example 6
[0078] The difference from Example 1 is that the water-soluble crystalline polymer is polyethylene glycol with a glass transition temperature of 55° C., and the rest is the same as Example 1.
[0079] Comparative Example 7
[0080] The difference from Example 1 is that the aqueous pressure-sensitive adhesive emulsion is an aqueous silicone pressure-sensitive adhesive emulsion, and the rest is the same as Example 1.
[0081] Experiment 1
[0082] The samples obtained in the embodiment and the comparative example were cut into strips with a width of 20 mm. A universal testing machine clamp was used to clamp PEN at one end and GDL at the other end for a shear peel test. The peel rate was 10 mm / min. The shear bond strength between GDL and PEN was tested. The experimental data are shown in Table 1.
[0083] Experiment 2
[0084] The GDL and PEN bonding samples of the above embodiment and comparative example were respectively installed in a fixture with a clamping pressure of 10 MPa. The fixture was placed in an environmental box at 85°C and 85% RH. After 1000 hours, the migration behavior of the adhesive in the GDL was observed. The experimental results are shown in FIG. Figure 1-6 .
[0085] Table 1 GDL and PEN substrate bonding strength test
[0086]
[0087]
[0088] According to the comparison between Comparative Example 1 and Example 1 in Table 1, the water-based modified pressure-sensitive adhesive in Comparative Example 1 only includes water-based acrylic pressure-sensitive adhesive, and the shear bonding strength between GDL and PEN is much lower than that in Example 1, indicating that the addition of a suitable amount of a relatively rigid polymer can improve the rigidity of the mixed adhesive and thus improve the bonding between GDL and PEN. In addition, after the high temperature, high humidity and high pressure simulation test of Experiment 2, very obvious migration traces of the water-based acrylic pressure-sensitive adhesive can be observed on the back of the GDL of the sample in Comparative Example 1, and the glue line is significantly widened (such as Figure 2 There is no trace of glue migration on the back of the GDL of the sample in Example 1 (as shown in the circle in the middle). Figure 1 This is because the commercially available water-based acrylic pressure-sensitive adhesive is prone to overflow, and cannot effectively inhibit the migration of the pressure-sensitive adhesive in the GDL while meeting the requirement of good adhesion between the GDL and the substrate at room temperature during GDL dispensing.
[0089] According to the comparison between Comparative Example 2 and Example 1 in Table 1, the shear bonding strength between GDL and PEN in Comparative Example 2 is much lower than that in Example 1. This is because the amount of water-soluble crystalline polymer added is too large, causing the pressure-sensitive adhesive to lose its initial adhesion, making it difficult to bond GDL and PEN at room temperature, and failing to meet the process requirements of GDL dispensing and MEA seven-in-one bonding.
[0090] According to the comparison of Comparative Example 1, Comparative Example 3 and Example 1 in Table 1, the shear bonding strength between GDL and PEN in Comparative Example 3 is basically close to that in Comparative Example 1, but much lower than that in Example 1, indicating that although too little addition of water-soluble crystalline polymer does not reduce the initial adhesion of the pressure-sensitive adhesive, it cannot effectively improve the bonding strength between GDL and PEN. At the same time, Figure 3 As shown, migration traces of the pressure-sensitive adhesive can still be observed on the back of the sample GDL in comparative example 3 of experiment 2, indicating that too little addition of rigid polymer cannot effectively inhibit the migration of the pressure-sensitive adhesive in a high temperature, high humidity and high pressure environment.
[0091] According to the comparison between Comparative Example 4 and Example 1 in Table 1, the addition amount of acrylamide monomer and crosslinking agent in Comparative Example 4 is too low. Although the shear bonding strength between GDL and PEN is basically close to that in Example 1, a small amount of migration traces of pressure-sensitive adhesive can still be observed on the back of the GDL of the sample in Comparative Example 4 after the high temperature, high humidity and high pressure simulation test of Experiment 2 (such as Figure 4 This is because the amount of acrylamide monomer and cross-linking agent added is too low to form a cross-linking under high temperature conditions to further strengthen the pressure-sensitive adhesive, resulting in migration marks of the pressure-sensitive adhesive on the back of the GDL.
[0092] According to the comparison between Comparative Example 5 and Example 1 in Table 1, it can be obtained that the amount of acrylamide monomer and cross-linking agent added in Comparative Example 5 is too high, which will affect the initial performance of the pressure-sensitive adhesive during GDL dispensing, resulting in poor bonding effect between GDL and PEN and deformation of the pressure-sensitive adhesive during press-packing.
[0093] According to the comparison between Comparative Example 6 and Example 1 in Table 1, the glass transition temperature of the high molecular weight polymer in Comparative Example 6 is lower, and the enhancement of the initial bonding performance between GDL and PEN is weaker than that of the polymer with greater rigidity in Example 1. At the same time, a small amount of migration traces of the pressure-sensitive adhesive can still be observed on the back of the GDL of the sample in Comparative Example 6 after the high temperature, high humidity and high pressure simulation test of Experiment 2 (such as Figure 5 This is because the glass transition temperature of the polymer added in Comparative Example 6 is lower than the upper limit temperature of 60-80°C of the normal operating temperature of PEMFC, and the degree of improvement in the rigidity of the pressure-sensitive adhesive is limited. After the accelerated test and therefore the higher experimental temperature of Experiment 2, migration marks of the pressure-sensitive adhesive may still appear on the back of the GDL.
[0094] According to the results of the high temperature, high humidity and high pressure simulation experiment of Experiment 2 ( Figure 1 and Figure 6As shown in the middle circle, it can be seen that since the comparative example 7 uses a high glass transition temperature polymer that cannot form hydrogen bond interaction with the added polymer and the two are difficult to be compatible, the added high glass transition temperature polymer cannot effectively enhance the pressure-sensitive adhesive to inhibit the penetration of the pressure-sensitive adhesive during the lamination of the GDL and the frame material and the subsequent battery stack process.
[0095] According to Examples 1-4 and Comparative Examples 1-6 in Table 1, the shear bonding strength between GDL and PEN in Examples 1-4 is improved, and the reason may be that the high glass transition temperature polymer improves the strength of the adhesive layer, so that its breaking strength is improved, meeting the process requirements of GDL room temperature bonding. At the same time, after the high temperature, high humidity and high pressure accelerated test, there is no trace of glue migration on the back of the GDL samples in Examples 1-4, which shows that the present invention is not less than or even enhances the bonding between GDL and PEN without affecting the GDL dispensing process, and can effectively suppress the overflow problem of ordinary unmodified commercially available pressure-sensitive adhesives.
[0096] In summary, adding a high Tg water-soluble crystalline polymer that can form hydrogen bonds with the pressure-sensitive adhesive molecules and an appropriate amount of acrylamide polymerization system to the commercially available water-based acrylic pressure-sensitive adhesive or polyurethane pressure-sensitive adhesive can effectively inhibit the migration of the pressure-sensitive adhesive in the GDL while ensuring good bonding between the GDL and the substrate at room temperature during GDL dispensing.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A water-based modified pressure-sensitive adhesive, characterized in that: The water-based modified pressure-sensitive adhesive comprises a water-based pressure-sensitive adhesive emulsion, a water-soluble crystalline polymer and polyacrylamide, wherein the polyacrylamide is obtained by reacting acrylamide monomer, a free radical initiator and a cross-linking agent, the water-based pressure-sensitive adhesive emulsion is an acrylate water-based pressure-sensitive adhesive or a polyurethane water-based pressure-sensitive adhesive, the glass transition temperature of the water-soluble crystalline polymer is greater than 90° C., and the water-soluble crystalline polymer contains a hydrogen bond donor functional group or a hydrogen bond acceptor functional group; The water-soluble crystalline polymer accounts for 10-150% of the solid mass of the water-based pressure-sensitive adhesive; the acrylamide monomer accounts for 1-10% of the total mass of the water-based pressure-sensitive adhesive solid and the water-soluble crystalline polymer; and the cross-linking agent accounts for 0.5-5% of the mass of the acrylamide monomer.
2. The water-based modified pressure-sensitive adhesive according to claim 1, characterized in that: The free radical initiator is 0.5-2% of the mass of the acrylamide monomer.
3. The water-based modified pressure-sensitive adhesive according to claim 1, characterized in that: The hydrogen bond donor functional group is at least one of an amide bond, a carboxylate, a sulfonate, a hydroxyl, a primary amine, and a secondary amine.
4. The water-based modified pressure-sensitive adhesive according to claim 3, characterized in that: The water-soluble crystalline polymer is at least one of polyacrylamide, urea-formaldehyde resin, polyallylamine, perfluorosulfonic acid resin and polyacrylic acid.
5. The water-based modified pressure-sensitive adhesive according to claim 1, characterized in that: The hydrogen bond acceptor functional group is at least one of an ether bond, a tertiary amine, an epoxy bond, a hydroxyl group, a carboxylic acid, an amide bond, a carboxylate group, a sulfonate group, and a carbon-fluorine bond.
6. The water-based modified pressure-sensitive adhesive according to claim 5, characterized in that: The water-soluble crystalline polymer is at least one of polyvinyl alcohol, polyethylene oxide, urea-formaldehyde resin, perfluorosulfonic acid resin and polyacrylic acid.
7. The water-based modified pressure-sensitive adhesive according to claim 1, characterized in that: The free radical initiator is a 60-80°C thermal initiator.
8. The method for preparing the water-based modified pressure-sensitive adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: adding acrylamide monomer, free radical initiator and crosslinking agent to the aqueous solution of water-soluble crystalline polymer at a temperature of 20-60° C., mixing evenly to obtain a mixed aqueous solution; S2: Add water-based pressure-sensitive adhesive latex to the mixed aqueous solution in S1 at a temperature of 20-60° C. and mix evenly to obtain a water-based modified pressure-sensitive adhesive.
9. Application of a water-based modified pressure-sensitive adhesive in a membrane electrode gas diffusion layer, characterized in that: The application comprises the following steps: coating the water-based modified pressure-sensitive adhesive described in any one of claims 1 to 7 on the surface of the porous layer of the gas diffusion layer, and pressing it with a five-in-one membrane electrode after drying to obtain a seven-in-one membrane electrode.
10. Use of the water-based modified pressure-sensitive adhesive in a membrane electrode gas diffusion layer according to claim 9, characterized in that: The pressing conditions are: pressure 0.05-0.5Mpa, pressing time 1-60s.
Citation Information
Patent Citations
Reinforcing material for solid polymer fuel cell, and cohesive / adhesive composition for use in same
CN103582562A
Binder for promoting binding force between gas diffusion layer of fuel cell and CCM interface and preparation method thereof
CN112838222A